Accounting information system for school cash receipts at SMA Krista Mitra Semarang - Debby Ramona Wijaya (Indonesia Auditing Research Journal, 2023)
The scope of the discussion of the system includes the process of class data collection, student data collection, bill payment transaction data collection and payment transaction data collection at Krista Mitra Semarang High School. Whereas the current system, even though in its implementation, does not experience many errors either in terms of data recording or calculations, the speed and accuracy of data factors will be better if a new computer-based system is implemented. The increase in students at Krista Mitra Semarang High School is expected to be easily handled by the new system. These conveniences include entering, storing and searching for certain data if needed at any time either for research materials or as analysis material for the parties concerned. Another convenience is in making the report.